2016
DOI: 10.1080/15476286.2016.1184387
|View full text |Cite
|
Sign up to set email alerts
|

Transient overexpression of exogenous APOBEC3A causes C-to-U RNA editing of thousands of genes

Abstract: APOBEC3A cytidine deaminase induces site-specific C-to-U RNA editing of hundreds of genes in monocytes exposed to hypoxia and/or interferons and in pro-inflammatory macrophages. To examine the impact of APOBEC3A overexpression, we transiently expressed APOBEC3A in HEK293T cell line and performed RNA sequencing. APOBEC3A overexpression induces C-to-U editing at more than 4,200 sites in transcripts of 3,078 genes resulting in protein recoding of 1,110 genes. We validate recoding RNA editing of genes associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 29 publications
7
97
0
Order By: Relevance
“…RNA editing gene targets was enriched for ontologies of methyltransferase activity, nuclear transport, DNA helicase and ubiquitin proteasome pathway (Supplementary Table S5). RNA editing at 90 sites was also catalyzed by A3A (Supplementary Table S6) which causes C>U RNA editing of 4,374 sites in the 293T overexpression system31. This finding suggests that although a small overlap exists among the edited sites of A3A and A3G, RNA editing targets of these two enzymes are largely distinct and that A3A has a broader target profile than A3G.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…RNA editing gene targets was enriched for ontologies of methyltransferase activity, nuclear transport, DNA helicase and ubiquitin proteasome pathway (Supplementary Table S5). RNA editing at 90 sites was also catalyzed by A3A (Supplementary Table S6) which causes C>U RNA editing of 4,374 sites in the 293T overexpression system31. This finding suggests that although a small overlap exists among the edited sites of A3A and A3G, RNA editing targets of these two enzymes are largely distinct and that A3A has a broader target profile than A3G.…”
Section: Resultsmentioning
confidence: 94%
“…However, recently we described that APOBEC3A (A3A) induces widespread site-specific C-to-U (C>U) RNA editing of cellular transcripts in pro-inflammatory macrophages and in monocytes exposed to hypoxia and/or interferons30. We also showed that the RNA editing function of A3A can be recapitulated by transient overexpression of A3A in 293T cells which causes site-specific RNA editing of thousands of transcripts31. Moreover, the majority (75%) of genes that are RNA-edited in the 293T overexpression system are also edited in monocyte-enriched PBMCs (MEPs) exposed to hypoxia and interferon type 1.…”
mentioning
confidence: 97%
“…Interestingly, APOBEC3A (A3A), another member of the cytidine deaminase family that is structurally related to APOBEC1 and is expressed primarily in myeloid cells, including monocytes and macrophages, has been identified as a novel C-to-U RNA editing enzyme (27,28). A3A functions in the inhibition of retrotransposons and several viruses including HIV-1 (human immunodeficiency virus type 1), HTLV1 (human T-cell lymphotropic virus type 1), HPV (human papillomavirus), parvovirus, and hepatitis B.…”
Section: C-to-u Rna Editing In Mammalsmentioning
confidence: 99%
“…A3A functions in the inhibition of retrotransposons and several viruses including HIV-1 (human immunodeficiency virus type 1), HTLV1 (human T-cell lymphotropic virus type 1), HPV (human papillomavirus), parvovirus, and hepatitis B. The transcripts of hundreds of genes, including implicated viral pathogenesis, Alzheimer's disease, peripheral blood monocytes exposed to hypoxia and/or interferons, and M1 (proinflammatory) macrophage differentiation, undergo site-specific C-to-U RNA editing (27,28).…”
Section: C-to-u Rna Editing In Mammalsmentioning
confidence: 99%
“…The APOBEC3 (A3) family of cytidine deaminases restricts endogenous retroelements thousands of genes undergo site-specific editing [Sharma et al, 2016a]. Furthermore, we 64 demonstrated site-specific editing of ssRNA with purified recombinant A3A in vitro, whereas 65 DNA editing is non-specific and occurs at multiple TC nucleotides (edited C underlined) 66 [Sharma et al, 2015].…”
mentioning
confidence: 88%